DIALOGIC READING AS A POTENTIAL ACTIVITY TO FACILITATE THE LEARNING OF LISTENING AND SPEAKING SKILLS - Maria Teodora Ping (Siliwangi University, 2017)
This paper will address the potentials of implementing a modified version of a particular shared book reading activity called ‘Dialogic Reading’ as an alternative activity to facilitate the learning of listening and speaking skills of EFL learners. Dialogic reading itself is defined as a form of shared book reading activity in the form of a dialogue between the readers (usually between or among adults and children, both in a one-on-one or a small group reading setting). To date, the existing studies have indicated that Dialogic Reading is an effective activity for young learners to learn basic reading skills, vocabulary, oral language and narrative skills (Whitehurst, 1992; Zevenbergen Whitehurst, 2002; Ping, 2014; Ping Syamdianita, 2015). However, considering the highly interactive, input-rich, multimodal learning environment that Dialogic Reading brings, this activity can also possibly be adapted and modified to facilitate the learning of listening and speaking skills for learners of different age groups and levels. Therefore, in this talk, I will discuss firstly the conceptual framework and then report the recent empirical study on the implementation of Dialogic Reading to improve young adult EFL learners’ receptive and productive skills I have been conducting starting early this year.